A study of prevalence of peripheral arterial disease in type 2 diabetes mellitus using ankle-brachial index and its correlation with coronary artery disease and its risk factors - Sharma, R. K.; Sandhu, Pashaura S.; Chhabra, Ajay; Singh, Jagbir; Kharbanda, Rajat (International Journal of Research in Medical Sciences, 2019)
Background: Peripheral arterial disease (PAD) is one of the macrovascular complications of type 2 diabetes mellitus (T2DM). There is significant difference in the reported prevalence of PAD and its associated risk factors between Indian and Western studies. The purpose of this study was to examine the PAD complicating T2DM, in particular the influence of PAD on the risk of CAD. Methods: Randomly selected 100 T2DM patients presented to Guru Nanak Dev hospital were included. In addition to a detailed history and physical examination, anthropometric parameters like body mass index was measured. CAD in patients was diagnosed by a history of angina, ECG changes, any past history of CAD or any treatment taken for CAD. Ankle brachial index (ABI) was measured. Data was collected systematically and analyzed according to the standard statistical methods. Results: The prevalence of PAD was 15%. CAD was present in 31%. PAD was found to be significantly correlated with age, duration of diabetes, smoking, systolic blood pressure, diastolic blood pressure, prevalence of BMI >25 kg/m2, HbA1c and serum HDL ≤40 mg%. Old age, high HbA1c level, and dyslipidaemia were found to be significant independent predictors of CAD. Conclusions: Using ABI authors found evidence of PAD in 15% patients of T2DM. The prevalence of CAD was higher in patients with PAD. So, there is definite and strong correlation between PAD and CAD. Thus, the early diagnosis of PAD should alert the clinician to a high probability of underlying CAD.